Healthcare provider and medical cannabis patient communication regarding referral and medication substitution: the Canadian context - Alexis Holman; Daniel J. Kruger; Philippe Lucas; Kaye Ong; Rachel S. Bergmans; Kevin F. Boehnke (BMC, 2022)
Abstract Background Patients use medical cannabis for a wide array of illnesses and symptoms, and many substitute cannabis for pharmaceuticals. This substitution often occurs without physician oversight, raising patient safety concerns. We aimed to characterize substitution and doctor-patient communication patterns in Canada, where there is a mature market and national regulatory system for medical cannabis. Methods We conducted an anonymous, cross-sectional online survey in May 2021 for seven days with adult Canadian federally-authorized medical cannabis patients (N = 2697) registered with two global cannabis companies to evaluate patient perceptions of Primary Care Provider (PCP) knowledge of medical cannabis and communication regarding medical cannabis with PCPs, including PCP authorization of licensure and substitution of cannabis for other medications. Results Most participants (62.7%, n = 1390) obtained medical cannabis authorization from their PCP. Of those who spoke with their PCP about medical cannabis (82.2%, n = 2217), 38.6% (n = 857) reported that their PCP had "very good" or "excellent" knowledge of medical cannabis and, on average, were moderately confident in their PCP's ability to integrate medical cannabis into treatment. Participants generally reported higher ratings for secondary care providers, with 82.8% (n = 808) of participants rating their secondary care provider's knowledge about medical cannabis as "very good" or "excellent." Overall, 47.1% (n = 1269) of participants reported substituting cannabis for pharmaceuticals or other substances (e.g., alcohol, tobacco/nicotine). Of these, 31.3% (n = 397) reported a delay in informing their PCP of up to 6 months or more, and 34.8% (n = 441) reported that their PCP was still not aware of their substitution. Older, female participants had higher odds of disclosing cannabis substitution to their PCPs. Conclusion Most of the surveyed Canadian medical cannabis patients considered their PCPs knowledgeable about cannabis and were confident in their PCPs' ability to integrate cannabis into treatment plans. However, many surveyed patients substituted cannabis for other medications without consulting their PCPs. These results suggest a lack of integration between mainstream healthcare and medical cannabis that may be improved through physician education and clinical experience.